On the Schrödinger-parabolic equation with multipoint nonlocal boundary condition - Yıldırım Özdemir (E-Journal of Analysis and Applied Mathematics)
The nonlocal boundary value problem for a Schrödinger-parabolic equation with multipoint nonlocal boundary conditions is examined. Stability estimates for the solution of this problem are established. Additionally, these stability estimates are applied to a mixed-type boundary value problem for the Schrödinger-parabolic equation with multipoint nonlocal boundary conditions.